Water build-up and evolution during the start-up of a PEMFC: Visualization by means of Neutron Imaging. (11th May 2017) - Iranzo, Alfredo; Salva, Antonio; Boillat, Pierre; Biesdorf, Johannes; Tapia, Elvira; Rosa, Felipe
Abstract: A commercial 50 cm 2 PEM fuel cell with serpentine flow fields was operated at 2.0 bar (a) and 60 °C with different relative humidity (RH) values for the inlet reactants (a matrix of 3 RH for anode and 3 RH for cathode). Between each test the cell was decompressed and liquid water was thus flushed out. The liquid water build-up and the time evolution during each experiment were recorded by means of Neutron Imaging. A qualitative and quantitative analysis of the results is presented in this work. It was observed that the dynamics of water build-up comprises three main stages, where the major difference is the liquid water accumulation rate. The onset location for the water appearance in the flow field channels was found to be determined by the flow field design, gravity and gas flow direction along the serpentine path. The time evolution of the water progressive accumulation along the flow field channels and cell active area is discussed. Highlights: Transient water build-up and evolution of the liquid water content is addressed. Three main stages were observed for the dynamics of the water build-up. Liquid water appears first in soft components, then in channels at lower U-bends. Water slugs enlarge along channels preferentially in the bottom-to-top direction. Neutron radiograph movies for transient experiments are presented (online version).